Efektivitas Pendidikan Kesehatan terhadap Peningkatan Pengetahuan Remaja tentang Infeksi Menular Seksual di SMK Tamansiswa Boja Kendal - Neka Victorria Rahim Maha Rizki; Widya Mariyana; Qomariyah Qomariyah (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Adolescents represent an age group highly susceptible to health issues, particularly sexually transmitted infections (STIs), due to limited knowledge and restricted access to accurate information. This study aimed to examine the effectiveness of health education in improving adolescents’ knowledge about STIs at SMK Tamansiswa Boja Kendal. The study employed a quantitative pre-experimental method using a one-group pretest-posttest design. A total of 32 students were selected using accidental sampling. The intervention consisted of health education delivered through booklets and posters. Data were collected using a structured questionnaire and analyzed using the Wilcoxon test. Findings revealed a substantial increase in knowledge after the intervention. Prior to the education, 96.9% of respondents demonstrated low knowledge, and only 3.1% had sufficient understanding; after the intervention, 100% of participants achieved a high level of knowledge. The Wilcoxon test yielded a significance value of p = 0.000 (p < 0.05), indicating a statistically meaningful difference before and after the intervention. These results confirm that health education is effective in enhancing adolescent understanding of STIs. Similar programs are recommended to be implemented regularly in educational settings as part of reproductive health promotion and disease prevention efforts..